Biosorption Of Cu (II) Ions Onto Base Treated Sugarcane Bagasse / Siti Raihan Zakaria and Megat Ahmad Kamal Megat Hanafiah - Zakaria, Siti Raihan; Megat Hanafiah, Megat Ahmad Kamal (2011)
The adsorption of Cu (ll) ions from aqueous solutions using agricultural waste particularly sugarcane bagasse that have been treated with base or Chemically Treated Sugarcane Bagasse (CTSB) was performed under batch mode. Batch experiments were conducted to determine the factors affecting adsorption such as pH. initial heavy metal concentration and contact time, The batch experiment showed that pH3-5 was the best range for the sorption of copper ions. Adsorption was fast as equilibrium was achieved within 60 minutes, and was best described by the pseudo-second order model. According to the Langmuir model, the maximum adsorption capacity of Cu (ll) ions was 23.81 mg g-I. The highest amount of heavy metal adsorbed occurred at pH 5 with shaking speed of 120 rpm. This study showed that CTSB can be used as good adsorbent materials for Cu (ll) removal/rom aqueous solution.